To find the answer, we need to calculate (12/15) * 10 ounces.
(12/15) * 10 = (4/5) * 10 = 8.
Therefore, there are 8 ounces in 12 of 15 of a 10-ounce block of cheese.
How many ounces are in 12 of 15 of a 10-ounce block of cheese
9 answers
How many ounces are in 1 over 2 of 1 over 5 of a 10-ounce block of cheese
To find the answer, we need to calculate (1/2) * (1/5) * 10 ounces.
(1/2) * (1/5) * 10 = 1/10 * 10 = 1.
Therefore, there is 1 ounce in 1 over 2 of 1 over 5 of a 10-ounce block of cheese.
(1/2) * (1/5) * 10 = 1/10 * 10 = 1.
Therefore, there is 1 ounce in 1 over 2 of 1 over 5 of a 10-ounce block of cheese.
A group of 9 people won 1/5 of a $4,500 prize. How much money did each person in the group win?
To find the amount of money each person won, we need to divide the total prize money won by the number of people in the group.
1/5 of $4,500 is calculated by (1/5) * $4,500 = $900.
Therefore, each person in the group won $900.
1/5 of $4,500 is calculated by (1/5) * $4,500 = $900.
Therefore, each person in the group won $900.
−2)×(15)÷(23)×(−56)÷(34)
To calculate this expression, we follow the order of operations, which is parentheses, exponents, multiplication/division (from left to right), and finally addition/subtraction (from left to right).
(-2) × (15) ÷ (23) × (-56) ÷ (34)
Let's simplify this step by step:
Step 1: (-2) × (15) = -30
(-30) ÷ (23) × (-56) ÷ (34)
Step 2: -30 ÷ 23 ≈ -1.3043 (rounded to 4 decimal places)
(-1.3043) × (-56) ÷ (34)
Step 3: (-1.3043) × (-56) = 73.2608 (rounded to 4 decimal places)
73.2608 ÷ 34 ≈ 2.1571 (rounded to 4 decimal places)
Therefore, the value of the expression is approximately 2.1571.
(-2) × (15) ÷ (23) × (-56) ÷ (34)
Let's simplify this step by step:
Step 1: (-2) × (15) = -30
(-30) ÷ (23) × (-56) ÷ (34)
Step 2: -30 ÷ 23 ≈ -1.3043 (rounded to 4 decimal places)
(-1.3043) × (-56) ÷ (34)
Step 3: (-1.3043) × (-56) = 73.2608 (rounded to 4 decimal places)
73.2608 ÷ 34 ≈ 2.1571 (rounded to 4 decimal places)
Therefore, the value of the expression is approximately 2.1571.
−2)×(15)÷(23)×(−56)÷(34) in fraction
To write the expression (-2) × (15) ÷ (23) × (-56) ÷ (34) as a fraction, we can simplify it step by step:
Step 1: (-2) × (15) = -30
Step 2: -30 ÷ 23 = -30/23
Step 3: (-30/23) × (-56) = (30/23) × (56) = 1680/23
Step 4: (1680/23) ÷ 34 = (1680/23) ÷ (34/1) = (1680/23) * (1/34) = 1680/782
Therefore, (-2) × (15) ÷ (23) × (-56) ÷ (34) can be written as the fraction 1680/782.
Step 1: (-2) × (15) = -30
Step 2: -30 ÷ 23 = -30/23
Step 3: (-30/23) × (-56) = (30/23) × (56) = 1680/23
Step 4: (1680/23) ÷ 34 = (1680/23) ÷ (34/1) = (1680/23) * (1/34) = 1680/782
Therefore, (-2) × (15) ÷ (23) × (-56) ÷ (34) can be written as the fraction 1680/782.